A two-dimensional model of the vanadium–cerium redox flow battery. (20th December 2019) - Smith, Scott; Firdous, Irum; Wang, Qiuhong; Esmalla, Salve; Daoud, Walid A.
Abstract: Redox flow batteries (RFB) provide efficient storage of renewable energy facilitating sustainable energy supply. Among various RFB, the vanadium cerium battery is distinguished with large storage potential and without phase transition during the redox reactions. Herein, a two-dimensional model of a slice of the cell in a vanadium cerium redox flow battery is developed for the first time. Electrochemical characterization of both the V(II)/V(III) and Ce(III)/Ce(IV) electrochemical systems in mixed acid media is conducted to obtain the key parameters of the model. The data obtained from the simulations is then validated against the results of real flow battery experiments exhibiting a good agreement. With the perspective of state-of-the-art design in RFB system management for future large-scale systems, state of charge deviation and flow efficiency, are introduced as innovative measures of lifetime and energy density of the battery. The illustrated effect of several parameters involved in the proposed model provides direction toward optimum design of RFB systems. Highlights: A two-dimensional model of the vanadium cerium redox flow battery is developed for the first time. A new character of flow efficiency is proposed to deliver a more comprehensive understanding of battery performance. State of charge (SOC) deviation is introduced depending on the SOCs in each half cell for a concise condition of the cell. Analysis of the impacts of physical parameters provides guidelines for design and utility demonstration of the model.